2017
DOI: 10.1002/ijch.201600078
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Proteins as Regulators of Beta‐amyloid Aggregation and Toxicity

Abstract: Amyloid disorders, such as Alzheimer’s, are almost invariably late-onset diseases. One defining diagnostic feature of Alzheimer’s disease is the deposition of beta-amyloid as extracellular plaques, primarily in the hippocampus. This raises the question: are there natural protective agents that prevent beta-amyloid from depositing, and is it loss of this protection that leads to onset of disease? Proteins in cerebrospinal fluid (CSF) have been suggested to act as just such natural protective agents. Here, we de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 132 publications
(175 reference statements)
0
16
0
Order By: Relevance
“…Amyloid plaques or senile plaques mostly consist of the Aβ peptides, the essential peptide whose presence at a nanomolar concentration is shown by numerous studies in the cerebrospinal fluid (CSF) as well as in serum [ 119 , 120 ]. However, the TASTPM animal model study pointed out that the concentration of Cu in the Alzheimer’s brain does not link to plaques deposition [ 121 ].…”
Section: Copper Ion Implication In Admentioning
confidence: 99%
“…Amyloid plaques or senile plaques mostly consist of the Aβ peptides, the essential peptide whose presence at a nanomolar concentration is shown by numerous studies in the cerebrospinal fluid (CSF) as well as in serum [ 119 , 120 ]. However, the TASTPM animal model study pointed out that the concentration of Cu in the Alzheimer’s brain does not link to plaques deposition [ 121 ].…”
Section: Copper Ion Implication In Admentioning
confidence: 99%
“…TTR, a 55 kDa homotetramer 14 with a dimer of dimers quaternary structure, is a protein present in the serum and cerebrospinal fluid 15 (CSF) that carries retinol and the thyroid hormone thyroxine (T4) 16 . The stability of the tetrameric form of TTR plays a pivotal role in the amyloidogenic properties of the native protein and its mutants 17,18 , which are in the cause of a series of severe amyloid diseases, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Cystatin C, a biomarker of renal function (Grubb et al ), is a small (13.3‐kDa) basic protein expressed by all nucleated cells. Notably, cystatin C is more abundant in the central nervous system, especially in the cerebrospinal fluid and brain tissues (Turk et al ; Pate and Murphy ). Recent studies have demonstrated that the expression of cystatin C is increased in stroke (Xiao et al ; Yang et al ) and that this increase seems to be a compensatory response that has a protective effect against ischemic brain injury (Ni et al ; D'Adamio ; Yang et al ).…”
mentioning
confidence: 99%